Venous-phase chest CT with reduced contrast medium dose: utilization of spectral low keV monoenergetic images improves image quality - Hickethier, Tilman; Chang, De-Hua (European journal of radiology, 2020)
Purpose - Intravenous contrast administration is crucial in many CT examinations but also poses a potential risk to the patient. Monoenergetic images (MonoE) of dual-energy CT systems can virtually increase iodine attenuation and might improve image quality (IQ) if contrast dose is reduced. In this study, we investigated the influence of MonoE on lymph node (LN) delineation and IQ in chest CT examinations with significantly reduced contrast dose (50 %) of a novel dual-layer CT (DLCT). - Method - 30 patients with clinically indicated reduced contrast dose underwent venous-phase chest DLCT scans. Conventional polyenergetic (PolyE) and MonoE images at 40keV were calculated. The contrast difference of hilar lymph nodes (LN-CD) to the adjacent right pulmonary artery, their signal-to-noise (SNR) and contrast-to-noise-ratio (CNR) were determined. Subjective IQ was evaluated by 2 readers with respect to LN delineation and overall contrast enhancement (CE) using a 5-point-Likert-scale. - Results - LN-CD, SNR and CNR were significantly higher in MonoE than in PolyE images (LN-CD 92.3±37.9 vs. 33.1±14.5 HU, SNR 8.4±3.4 vs. 4.0±1.2, CNR 9.2±6.3 vs. 2.6±1.5; all p<0.01). The LN delineation (3.7±0.9 vs.1.8±0.7; p<0.01) and the CE (3.9±0.7 vs. 2.3±0.7; p<0.01) were rated significantly better for MonoE than for PolyE images. There was no MonoE examination classified as non-diagnostic. - Conclusions - Subjective and objective IQ parameters can be significantly improved for venous-phase chest CT examinations with reduced contrast doses by utilization of low-keV MonoE reconstructions. All MonoE images provided sufficient overall CE and therefore reduced contrast doses might be considered in a wider range of DLCT examinations and patients.